Effect of Mn on Corrosion Resistance of Low-Cr Weathering Steel - Guangbo Zhang; Huanhuan Zhang; Xingyu Liu; Yuchen Xin; Shubiao Yin; Lei Gao; Zhe Shi (Metals)
As the pace of human development in the ocean accelerates, the demand for corrosion-resistant building materials in marine engineering projects is constantly increasing. The development of high-performance corrosion-resistant materials and their mechanism research has gradually become the latest hotspot in the field of metal materials. Through cyclic dry–wet testing, electrochemical techniques, morphological characterization, and compositional analysis, this study simulated the impact of varying manganese content on weathering steel corrosion resistance in chloride environments. The results indicated that, compared to low-manganese weathering steel, the average rust layer thickness of high-manganese weathering steel increased by 22.5%. Additionally, manganese was found in the rust as MnO/MnO2, acting as a catalyst to promote electron transfer, which led to a decrease in the α/γ* ratio in the high-manganese weathering steel, thereby accelerating the corrosion reaction.